Critical Portrait of Vocational High School Accounting Teachers Sustainable Awareness in Indonesia - Sri Sumaryati; Ivada, Elvia; Susanti, Asri Diah; Nurhaini, Lies (JTP - Jurnal Teknologi Pendidikan, 2024)
about their actions’ environmental and social impact, Education teaches students to think critically and responsibly towards the surrounding environment. Therefore, as the spearhead of education, teachers must be aware of sustainability education, so that they can teach it to their students Hence. This research explores the knowledge, attitudes, and behaviors towards sustainable awareness, especially in accounting teachers, and analyzes the interdimensional relationship to sustainable awareness.  This research uses a quantitative approach with a survey type of research. The data source for this study is 277 Vocational High School accounting teachers from the program of the institution's accounting and finance expertise, consisting of 239 females, and 38 males. They all participated in Teacher Professional Education at Universitas Sebelas Maret  Surakarta in 2023. The instrument used in this study is the Sustainability Consciousness Questionnaire (SCQ), developed by Gericke et al. in 2019. As a result of this study, teachers have knowledge about sustainable awareness that is followed up with sustainable attitudes and behaviors even though they are not optimal. This result can be seen from the high average score on knowledge of sustainable awareness, not followed by a high score on sustainable attitudes and behaviors. The study results show that each component's scores are 3.44, 3.17, and 3.13. This means that knowledge of sustainable awareness is not balanced with sustainable attitudes and behaviors.